The determinants of capital structure: evidence from consumer sector in Malaysia / Anis Airin A'riffina@Azman - A'riffina@Azman, Anis Airin (2021)
Capital structure is the combination of capital from internal and external. The firm needs to mix both capital to run their business smoothly. Therefore, in order to generate long term funds, the management of the firm need to identify and knowing what factors that effect positively on capital structure for the company's growth and related assets. The main focus of this research is to justify the determinants of capital structure and how they are related to capital structure. This study is based on 20 companies selected from Bursa Malaysia in the consumer sector from the year 2015 to 2019. The models is using the debt equity ratio as the dependent variable. Besides, the independent variable representing by return on equity, current ratio, tangible assets to total assets and long term debt to total assets as the independent variables. All the independent variables will be test in order to see whether it is significance or not with the debt equity ratio by using a multiple regression analysis. Based on previous study, the independent variable of tangible assets to total assets ratio expected to have a positive relationship with the debt equity ratio while the independent variables of return on equity, current ratio and long term debt to total assets expected have mixed impact to debt equity ratio that can be either positive or negative relationship.